Is anticoagulant therapy necessary after hospitalization with COVID-19 pneumonia? - P. A. Davtyan; R. M. Gumerov; Sh. Z. Zagidullin; A. V. Samorodov; B. Cai; N. Sh. Zagidullin (Российский кардиологический журнал, 2022)
The coronavirus disease 2019 (COVID-19) pandemic is associated with high virulence, mortality and healthcare burden around the world. One of its features is procoagulant activity, which leads to a high incidence of thromboembolic events in the lungs and other organs. Therefore, from the very onset of the moderate COVID-19, low molecular weight heparins began to be used as anticoagulants, which proved to have a beneficial effect on mortality and the disease course and were included in all guidelines. However, the question on anticoagulant therapy need after discharge from the hospital is controversial. The opinions of various medical professional communities on this issue are divided. In particular, some of them, including the Russian Ministry of Health guidelines recommend 30-45day anticoagulation using novel oral anticoagulants (dabigatran, rivaroxaban, apixaban), but other sources do not provide such recommendations. This review discusses the effectiveness of anticoagulant therapy after COVID-19, as well as the need to use stratification scales to assess this therapy.